PENINGKATAN DAYA SAING RAKIK AYAH ASLI MELALUI MODERNISASI PRODUKSI, INOVASI KEMASAN (HAKI), DAN PEMASARAN DIGITAL - Saniro, Roma Kyo Kae; Zulfitri, Amelya; Sukmawati, Noni (Universitas Mataram, 2025)
The purpose of this community service is to increase the competitiveness of Rakik Ayah Asli through optimizing production and marketing at the national level. Rakik Ayah Asli, a West Sumatra-based MSME that produces rakik as a typical Minangkabau food, has excellent growth potential, but is constrained by limited production technology, quality variations, and a lack of digital marketing strategies. The implementation method includes socialization, production and marketing training, technology application, mentoring, and evaluation. Production training focused on using modern machines as a 15 kg Horizontal Dough Mixer, Gas Deep Fryer, and 5 kg oil draining Spinner. In contrast, marketing training emphasized digital marketing through Instagram and Shopee and packaging innovation with the support of HAKI registration. The implementation results showed an increase in production capacity of up to ± 120–150%, an increase in product quality consistency of ± 80%, and an improvement in packaging appeal of ± 70%. The digital marketing strategy succeeded in expanding market reach with an estimated increase in sales of ± 30% in the first three months. Furthermore, pretest–posttest results indicated increased workers' understanding of digital marketing (an average increase of 1 point) and packaging, although this remained variable. This activity concluded that the application of production technology, packaging innovation, and digital marketing has proven to be effective in increasing the competitiveness of Rakik Ayah Asli. Further support, product diversification, strengthening of digital strategies, and cross-sector partnerships are needed to ensure Rakik Ayah Asli's sustainability and become a competitive traditional Minangkabau culinary icon at the national level. Keywords: competitiveness, packaging innovation, Minangkabau, digital marketing, rakik ayah asli, production technology, MSMEs